Not Just Another Alternative School: Policy Problematization, Neoliberalism, and Racial Biopolitics. (January 2016) - Gulson, Kalervo N.; Webb, P. Taylor
In this article, we problematize the establishment of an Africentric Alternative School in Toronto, Canada. We argue that policy, and race and racializations cannot be understood outside of, or immune to, neoliberalism. We contend that policy is a form of racial biopolitics, and race is now produced through neoliberal markets, in conjunction with earlier, liberal categories. We conclude that neoliberalism has produced new forms of racial biopolitics; whereas the state is much less overtly involved in producing and arranging racializations. Instead, neoliberal education policy has transferred or downloaded these forms of racial biopolitics onto populations which are now "free" and "empowered" to produce and maintain variable raciologies.